DEVELOPMENT OF AN IDENTITY MANAGEMENT SYSTEM USING SINGLE SIGN ON WITH THE CENTRAL AUTHENTICATION SERVICE METHOD - Setiawan, Awan (Proceedings of KNASTIK, 2012)
This paper discusses the implementation of a method for single sign on (SSO) by usingCentral Authentication Service (CAS) and MySQL in a Web portal environment.Department of Informatics Faculty of Engineering Langlangbuana Univesity possesseda variety of web-based applications to support the academic activities, including webapplication libraries, application of laboratory management, and academicinformation systems. All access to these applications each needs a unique userauthentication for each user. This will cause the user login process many times. SingleSign On technologies provide convenience to the user to authenticate. Users only needto do a one-time login for access to all existing applications. Users do not have tomemorize numerous accounts, only one account and not have to repeatedly login, onesingle login is enough. It can also simplify user data in organizing existing datasecurity, so that the user is more secure, because it uses centralized user data storage.CAS used to handle communication problems between different web applications, so allthe applications can be integrated into a Web portal. MySQL is used as data storage,where all user data stored in a MySQL database.